Pedagogy of Argumentation: Teaching the Skills of Argumentation to Older Teens - Moskalyova, Luydmyla; Maksymov, Oleksandr; Gurov, Serhiy; Gurova, Tetyana; Yakovleva, Viktoria (Journal of History Culture and Art Research, 2020)
The article deals with the problem of training future teachers to teach older teens the ability of argumentation as an intellectual and communicative activity. The authors analyze the specifics of the training of future teachers in higher education institutions; the process of formation of the competence of teaching the ability of argumentation; the development of pedagogy of argumentation in higher education institutions. The current stage of the education system development requires improving the level of teachers’ training. The problem of professional competence of future teachers who acquire the method of teaching students the ability of argument is relevant. At the same time, there is a need to develop a special professional quality of the future teacher – to be able to defend their own point of view, to formulate theses, to effectively build a system of arguments during communication. So, the issue has a complex character – university students should be taught pedagogical argumentation, they should be equipped with the corresponding technique in order their future pupils gain an opportunity to realize successfully the structure of argumentation both in written and spoken communication. The purpose of the article is to determine the features of teaching methods used at secondary school when forming pupils’ ability of argumentation. This paper aims to identify the main approaches to teaching argumentation, to find out the level of future teachers’ readiness to teach students the ability of argumentation, to develop an experimental method of teaching pedagogy of argumentation and check its results. We conducted an experimental study with 44 students of the Bogdan Khmelnitsky Melitopol state pedagogical university and State Higher Educational Institution Krivoy Rog State Pedagogical University in Ukraine for two years (2018-2019). We divided students into control and experimental groups and provide an extensive education to the control group. The results suggest that the control group’s argumentation skills increased significantly. In drawing conclusions, we note that the proficiency of the teaching methods of older adolescents affects the professional and a future teacher’s personal qualities.